Comparison of cytotoxic effects of calcium silicate-based materials on human pulp fibroblasts - Mehmet Adıgüzel; Fuat Ahmetoğlu; Ayçe Ünverdi Eldeniz; Mehmet Gökhan Tekin; Bülent Göğebakan (Tabriz University of Medical Sciences, 2019)
Background. This study aimed to compare the in vitro cytotoxicity of Theracal LC, BiodentineTM, iRoot BP Plus, and MTA Angelus on human pulp fibroblasts (HPF). Methods. Fifteen discs from each calcium silicate-based material were prepared in sterile Teflon molds. After setting, the fabricated discs were eluated with a culture medium for 24 h. HPF cells were plated onto 24-well plates at 5×103 cells/well, and the cells were exposed to the material eluates. The cell viability was evaluated with MTT assay at three different times (24, 48, and 72 h). Data were statistically analyzed. The apoptotic/necrotic status of HPF cells exposed to material eluates was determined by flow cytometry. Results. The differences between the effects of Theracal LC, BiodentineTM, MTA Angelus, and iRoot BP Plus on HPF cells were found to be statistically significant (P<0.05). Theracal LC was found to be more cytotoxic considering other vital pulp capping materials at 24- (28.3%), 48- (44.9%), and 72-hour (49.2%) intervals. On the other hand, BiodentineTM showed the least cytotoxic effects (97.1%, 130.0%, and 103.7%, respectively) According to flow cytometry results, Theracal LC material increased apoptosis/necrosis ratios compared to the other materials. Conclusion. Based on the results of the present study, BiodentineTM, MTA Angelus, and iRoot BP Plus can be classified as biocompatible materials in vital endodontic treatments. However, the Theracal LC materials should be used carefully due to their cytotoxic effects.